Climate resilient cities : (The World Bank, 2009)
Climate Resilient Cities: A Primer on Reducing Vulnerabilities to Disasters provides city administrators with exactly what they need to know about the complex and compelling challenges of climate change. The book helps local governments create training, capacity building, and capital investment programs for building sustainable, resilient communities.